Encapsulation of Black Seed Oil in Alginate Beads as a pH-Sensitive Carrier for Intestine-Targeted Drug Delivery: In Vitro, In Vivo and Ex Vivo Study - Abul Kalam Azad; Sinan Mohammed Abdullah Al-Mahmood; Bappaditya Chatterjee; Wan Mohd Azizi Wan Sulaiman; Tarek Mohamed Elsayed; Abd Almonem Doolaanea (MDPI AG, 2020)
Black seed oil (BSO) has been used for various therapeutic purposes around the world since ancient eras. It is one of the most prominent oils used in nutraceutical formulations and daily consumption for its significant therapeutic value is common phenomena. The main aim of this study was to develop alginate-BSO beads as a controlled release system designed to control drug release in the gastrointestinal tract (GIT). Electrospray technology facilitates formulation of small and uniform beads with higher diffusion and swelling rates resulting in process performance improvement. The effect of different formulation and process variables was evaluated on the internal and external bead morphology, size, shape, encapsulation efficiency, swelling rate, in vitro drug release, release mechanism, ex vivo mucoadhesive strength and gastrointestinal tract qualitative and quantitative distribution. All the formulated beads showed small sizes of 0.58 ± 0.01 mm (F8) and spherical shape of 0.03 ± 0.00 mm. The coefficient of weight variation (%) ranged from 1.37 (F8) to 3.93 (F5) ng. All formulations (F1−F9) were studied in vitro for release characteristics and swelling behaviour, then the release data were fitted to various equations to determine the exponent (ns), swelling kinetic constant (ks), swelling rate (%/h), correlation coefficient (r2) and release kinetic mechanism. The oil encapsulation efficiency was almost complete at 90.13% ± 0.93% in dried beads. The maximum bead swelling rate showed 982.23 (F8, r2 = 0.996) in pH 6.8 and the drug release exceeded 90% in simulated gastrointestinal fluid (pH 6.8). Moreover, the beads were well distributed throughout various parts of the intestine. This designed formulation could possibly be advantageous in terms of increased bioavailability and targeted drug delivery to the intestine region and thus may find applications in some diseases like irritable bowel syndrome.